2013
DOI: 10.1002/jgrd.50485
|View full text |Cite
|
Sign up to set email alerts
|

Geostationary infrared methods for detecting lightning‐producing cumulonimbus clouds

Abstract: [1] This study documents the behavior of cloud top infrared (IR) fields known to describe physical processes associated with growing convective clouds, for 30 nonlightning and 33 cloud-to-ground (CG) lightning-producing convective storms. The goal is to define "critical" threshold values for up to 10 IR fields that delineate lightning from nonlightning convective storms. Meteosat Second Generation and United Kingdom Meteorological Office very low frequency arrival time difference satellite and lightning data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
0
7
0
2
Order By: Relevance
“…The authors documented that many of the flashes observed in thundersnow were associated with localized high‐ Z H and low‐ Z DR regions, suggesting regions with graupel production indicating that storms with lightning could have larger and more numerous graupel content than storms without lightning. Observations from ground‐based total lightning combined with Doppler and polarimetric radar [ Deierling and Petersen , ], numerical simulations with explicit microphysics [ Calhoun et al ., ], and satellite observations [ Mattos and Machado , ; Matthee and Mecikalski , ] also support this idea, and it is suggested that storms with lightning include better graupel growth conditions due the existence of stronger updrafts, higher supercooled water content, and ice particle mass.…”
Section: Resultsmentioning
confidence: 98%
“…The authors documented that many of the flashes observed in thundersnow were associated with localized high‐ Z H and low‐ Z DR regions, suggesting regions with graupel production indicating that storms with lightning could have larger and more numerous graupel content than storms without lightning. Observations from ground‐based total lightning combined with Doppler and polarimetric radar [ Deierling and Petersen , ], numerical simulations with explicit microphysics [ Calhoun et al ., ], and satellite observations [ Mattos and Machado , ; Matthee and Mecikalski , ] also support this idea, and it is suggested that storms with lightning include better graupel growth conditions due the existence of stronger updrafts, higher supercooled water content, and ice particle mass.…”
Section: Resultsmentioning
confidence: 98%
“…In order to better understand deep moist convection, some techniques of analysis have been used to identify or estimate different patterns in satellite images, such as initiation, cloud top glaciation, cold-U/V shape, and overshooting tops (Petersen et al, 1984;Guang and McFarlane, 1991;Morel and Senesi, 2002;Roberts and Rutledge, 2003;Setvak et al, 2003;Holloway and Neelin, 2007;Zinner et al, 2008;Bedka et al, 2010;Coning et al, 2010;Bedka, 2011;Mahovic and Mikus, 2011;Matthee and Mecikalski, 2013). Simple techniques, such as a nearest neighbor average or time trends, can show important information that highlight subtle features of severe weather.…”
Section: Methodsmentioning
confidence: 99%
“…For middle and high clouds, T b,6.2 , T b,6.9 , and T b,7.3 remain unchanged unless the cloud top reaches their peak weighting function levels. The BT difference (BTD) between channels 9 and 10 (i.e., T b,6.9 − T b,7.3 ) can be utilized for estimating whether a cloud has grown to a given altitude (Matthee and Mecikalski 2013). T b,6.9 − T b,7.3 is mostly negative (about −15 K) when the moist layer is at ~ 500 hPa, and meanwhile, the cloud top is lower than ~ 600 hPa.…”
Section: Interest Fields Selectionmentioning
confidence: 99%